2006
DOI: 10.1063/1.2189566
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic placement of single ferritin molecules

Abstract: We electrostatically placed a single ferritin molecule on a nanometric 3-aminopropyltriethoxysilane (APTES) pattern that was on an oxidized Si substrate. The numerical analysis of the total interaction free energy for ferritin predicted that a quadrilateral array of 15nm diameter APTES nanodisks placed at intervals of 100nm would accommodate a single molecule of ferritin in each disk under a Debye length of 14nm. The experiments we conducted conformed to theoretical predictions and we successfully placed a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 20 publications
3
70
0
1
Order By: Relevance
“…[16][17][18] Artificially biomineralized nanodots are uniform in size and shape due to the restricted inner cavity size and shape of protein shell. Chemical flexibility of protein outer surface made the formation of high-density two dimensional inorganic nanodot arrays 19 and selective deposition 20,21 possible, and vulnerability of protein made the selective removal of organic residues possible. It means that we can produce selectively placed high-density inorganic BND array from protein/BND nanoarchitecture.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Artificially biomineralized nanodots are uniform in size and shape due to the restricted inner cavity size and shape of protein shell. Chemical flexibility of protein outer surface made the formation of high-density two dimensional inorganic nanodot arrays 19 and selective deposition 20,21 possible, and vulnerability of protein made the selective removal of organic residues possible. It means that we can produce selectively placed high-density inorganic BND array from protein/BND nanoarchitecture.…”
Section: Introductionmentioning
confidence: 99%
“…However, electrostatic interaction is a long distance force and, in genral, is thought to be inappropriate for handling nanometric materials. Yoshii and Kumagai solved this issue by carrying out simulation of ferritin-substrate electrostatic interaction and showed that ferritin molecules can be placed on the substrate one by one [7][8][9].…”
Section: Resultsmentioning
confidence: 99%
“…6(a) and 6(b)]. 129) SiO 2 substrates and ferritin are negatively charged at neutral pH. Positively charged disks of 15 nm diameter were fabricated by electron beam lithography (EBL), and coated with 3-aminopropyl-triethoxysilane (APTES).…”
Section: Apoferritinmentioning
confidence: 99%
“…The nanopattern and size of the positively charged areas can be defined by the electron beam. 129,130) As another placement method for ferritin, diblock copolymers combined with electrochemical modification allow the selective deposition of ferritin in specific nanometer-size areas [ Fig. 6(c)].…”
Section: Apoferritinmentioning
confidence: 99%